PENGARUH STRATEGI DIFERENSIASI DAN PROMOSI ONLINE TERHADAP KEPUTUSAN PEMBELIAN PADA BUTIK MUTIARA SANI - Maulidia, Nia Darma (Magister Manajemen Universitas Wisnuwardhana, 2020)
This study aims to determine the effect of differentiation strategy and online promotion on purchasing decisions. This type of research is quantitative. The sampling technique used is the Probability Sampling technique with a sample of 98 respondents. The tool used in this study is multiple linear regression analysis, t test, F test. According to Setiyaningrum (2015:71), Positioning is the way a product is defined by consumers based on important attributes where the product is placed in the minds of consumers compared to rival products. . This positioning strategy must be able to be carried out by the company well in an effort to get customers and retain those customers. The results showed that the differentiation strategy and online promotion had a positive and significant effect on purchasing decisions. Mutiara Sani Boutique Management should maintain and further improve online promotions in various internet media and pay attention to the differentiation strategy process such as prioritizing service and product quality so that consumer purchasing decisions are increasing.